Interrelationship between gender and age and indicators of military professional-applied training as a prerequisite for preventing stress-associated risks through recreational physical activity - Shynkaruk , Oksana; Byshevets , Nataliia; Dutchak , Myroslav; Andrieieva , Olena; Yakovenko , Olena; Davydov , Denys (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Research on professional-applied training of military personnel during wartime is highly relevant, especially in the context of modern military conflicts and the increasing burden on soldiers. Professional-applied training has a significant impact on military personnel’s ability to act effectively in combat conditions, as well as on their psychological state and endurance. Prevention of stress-associated conditions in military personnel through physical activity will contribute to improving psychophysical health, enhancing overall condition, and emotional well-being of military personnel. The objective of this study was to determine the interrelationships between indicators of professional-applied training among military personnel in different age groups and by gender, and to evaluate the significance of various types of professional-applied training for performing combat tasks. Methods: analysis of specialized scientific literature, comparison, questionnaires, systematization, statistical analysis methods – data verification for adherence to the normal distribution law (Kolmogorov-Smirnov test), descriptive statistics (central tendency and dispersion Me (25; 75) units), χ2 criteria group (for verifying the distribution’s conformity to the general population’s uniform distribution; for independent samples, if all variables in the contingency table exceed 5, otherwise – Fisher’s exact test), rank-based analysis of variance using the Kruskal-Wallis H test (to determine statistically significant differences between various age groups of military personnel regarding their professional-applied training, comparing levels of professional-applied training among different age groups of military personnel). To study the correlations between indicators of military personnel’s professional-ap-plied training, Spearman’s correlation analysis (ρ) was used to assess the strength and direction of the relationship between different indicators. For interpreting Spearman’s correlation coefficients, we used a table for evaluating Spearman’s correlation coefficient. Participants. The study involved 4403 military personnel, with men comprising 89.9% of the participants. The age distribution of respondents was as follows: 28.9% were aged 21-30 years, 28.7% were 31-40 years, and 24.9% were 41-50 years. Soldiers accounted for 56.2% of the sample, with 69% belonging to the Air Force, and 30.1% had participated in combat operations in the past 6-12 months. Educational background was as follows: 34.9% had secondary education, 27.1% had vocational-technical education, and 38.0% had higher education. The study was conducted from February 27 to April 15, 2024. Results. The analysis included self-assessment of military personnel’s professional-applied training indicators, including psychological characteristics (reaction speed, decision-making speed, flexibility in decision-making, leadership qualities) and specialized skills (medical assistance, shooting, survival skills). Correlation analysis revealed that men’s professional training indicators significantly correlated with each other (Spearman’s ρ = 0.65), with a high level of correlation observed between reaction speed and the ability to make decisions in critical situations. In women, these correlations were less pronounced. Men’s professional-applied training indicators depended on age, while no clear age-related dynamics were observed in women. Respondents identified stress resistance, strategic thinking, leadership abilities, and agility as the most important characteristics of professional-applied training. Military personnel considered teamwork (55.1%), psychological endurance (49.2%), physical endurance (34.8%), and tactical skills (30.7%) to be the most significant types of professional-applied training for effective combat task performance. Conclusion. The study’s results are aimed at improving military personnel training programs, particularly in developing differentiated approaches that consider gender and age characteristics to enhance their effectiveness in performing combat tasks. The research highlighted the importance of stress resistance and strategic thinking as key characteristics for the successful execution of military duties.